Ranking of zoonotic diseases using composite index method: An illustration in Indian context - KURIAN, ARUN; DANDAPAT, PREMANSHU; JACOB, SHIJA; FRANCIS, JOSEPHINE (The Indian Journal of Animal Sciences, 2014)
This study illustrates the method of ranking the most important zoonotic diseases in India based on composite index method. Every reported zoonotic disease in India was ascertained a composite index, based on 7 indices or factors as follows: Incidence and prevalence of the disease in human and in animal populations, severity of the adverse health effects in humans, trends and distribution of the zoonotic disease in human and in animal populations, the economic loss in production and the negative impact on trade and industry. Based on these composite indices, the most important zoonotic diseases in India were identified and ranked accordingly. The 8 most important identified zoonoses ranked in the order of descending impact are: rabies, highly pathogenic avian influenza, anthrax, brucellosis, leptospirosis, bovine tuberculosis, Japanese encephalitis and porcine cysticercosis. Ranking based on the composite index method is highly useful in identifying the impacts of zoonotic diseases in diverse contexts. This will improve the decision making among planners at national and international levels, for better utilization and prioritization of available resources for the control and eradication of these diseases.